Genetically modified food and humanity's well-being: an Islamic perspective - Akhmetova, Elmira (Springer International Publishing, 2016)
The fundamental aim of science and knowledge in Islam is the search for truth in the way of benefitting mankind. Genetically modified technology is one of the significant achievements of modern science, which promises to create an essential sustainable way to feed the world and to provide food security. Farmers today widely adopt GM crops, which have been modified with traits intended to provide benefit to farmers, consumers and industry. These traits include improved shelf-life, disease resistance, stress resistance, herbicide resistance, and pest resistance, production of useful goods such as biofuel or drugs, and ability to absorb toxins. Yet, a number of recent researches object GM foods on several grounds, including safety and health issues, and environmental, political and economic concerns. Another fact for concern is that GM seeds and potentially animals are subject to intellectual property rights owned by multinational corporations. This paper accordingly reviews the issue of GM foods from religious, social and ethical-based perspectives. After discussing the constructive and doubtful aspects of GM foods, the paper suggests that more independent studies should be done on the safety of GM production. Also, it recommends introducing a mandatory labelling for foods containing GM ingredients since the buyers have the rights to know the quality and characteristics of the commodities at sell.